Metabolic reprogramming and M2 macrophage depletion define the microenvironment of adenomyosis - Bian, Xuejiao; Sun, Zhe; Lai, Junliang; Li, Boyu; Dong, Xinyi; Guan, Hengyu; Vankelecom, Hugo; Sun, Yun (Frontiers in Endocrinology, 2025)
BackgroundAdenomyosis is a chronic gynecological disorder characterized by the invasion of endometrial tissues into the myometrium of the uterus, with pathophysiology linked to chronic inflammation and metabolic dysregulation. However, the understanding of the molecular mechanisms and underlying pathologies remains limited. This study aims to elucidate the metabolic reprogramming and immune dysregulation within the eutopic endometrium from patients diagnosed with adenomyosis, and identify potential therapeutic targets or diagnostic indicators.MethodsWe analyzed publicly available microarray (GSE78851), bulk RNA-seq (GSE193928) and single-cell RNA-seq (Human Endometrial Cell Atlas) datasets to explore the microenvironment of eutopic endometrium from adenomyosis patients. Transcriptomic differences were assessed in GSE78851 (3 adenomyosis versus 5 controls), followed by immune composition and metabolic flux analysis. Findings on immune infiltration and metabolic changes were further validated in GSE193928 (6 adenomyosis versus 15 controls after quality control). Metabolic flux analysis was further extended to single-cell RNA sequencing data derived from endometrial samples of 63 donors. Key genes involved in keratan sulfate biosynthesis were further validated by RT-qPCR and immunofluorescence staining on endometrial biopsy samples.ResultsOur study revealed widespread reprogramming in eutopic adenomyosis endometrium, characterized by enhanced immune-related pathways, reduction of M2 macrophage abundance, and disrupted metabolic processes. Further investigation of scRNA-seq data highlighted the cell type-specific metabolic profiles and immune-metabolic interplay within the endometrial microenvironment. Notably, the dysfunction of keratan sulfate biosynthesis, coupled with reduced M2 macrophage level, emerged as a consistent feature. Importantly, four key genes involved in keratan sulfate biosynthesis, including CHST1, CHST6, B4GALT1, and B3GNT2, were upregulated in eutopic endometrium compared to controls, suggesting their potential role in the pathophysiology of the disease.ConclusionsThis study identifies dysregulation of keratan sulfate biosynthesis as a central feature of adenomyosis and links it to reduced M2 macrophage abundance and immune-metabolic imbalance. Validation of four keratan sulfate related genes strengthens their potential as biomarkers or therapeutic targets, providing novel mechanistic insight into the pathogenesis of adenomyosis.